جسمانی اور ذہنی صحت کے لیے اسلامی اخلاقی بنیادیں: Islamic Ethical Foundations for Physical and Mental Well-being - Dr. H. Saman Sarwar (Al-Amīr Research Journal for Islamic Studies, 2024)
Humankind is facing all sorts of conflicts. But instead of dealing peaceful means we are faced with is Darwinian resolution. “The Might is Right” concept, which is the powerful resort to force and impose their will on the weak; while, this mechanism may apply to others of God’s creation, it does not work for homo-Sapiens: Because we are endowed with a moral sense, which overshadows all behavior. This moral attitude requires tackling the underlying problem adequately. Unless it is tackled properly, the conflict persists: it does not go away and comes back in swear forms becoming ever more pernicious. The moral sense is strong in Islam. Islam means peace in all its form and asks for justice in resolving all conflicts. So it’s satisfied with the result and being at peace works for peace with all concerned. Islamic principles are very beneficial for our physical and mental health. Key Words: Conflict, Islamic principles, peace work, moral sense